Inhaled Corticosteroids Increase the Risk of Pneumonia in Patients With Chronic Obstructive Pulmonary Disease: A Nationwide Cohort Study. Issue 42 (October 2015) - Lee, Ming-Chia; Lee, Chih-Hsin; Chien, Shu-Chen; Chang, Jer-Hwa; She, Han-Lin; Wang, Jann-Yuan; Yu, Ming-Chih
Abstract : Abstract: The association of inhaled corticosteroids (ICS) and pneumonia in patients with chronic obstructive pulmonary disease (COPD) is still controversial. From the National Health Insurance Database of Taiwan, COPD cases with history of acute exacerbation (AE) were identified (COPD cohort). Time-dependent Cox regression analysis was applied to investigate the risk factors for pneumonia with COPD severity controlled by surrogate variables. Among the COPD cohort, those who continuously used ICS for more than 360 days without interruption were selected (ICS cohort). The incidence rate of pneumonia during ICS use was compared with those before ICS use and after ICS discontinuation by using pair t test. A total of 6034 and 842 cases were identified as the COPD and ICS cohorts, respectively. In the COPD cohort, recent ICS use was independently associated with pneumonia (hazard ratio: 1.06 [1.02–1.11] for per 80 mg of budesonide). Other independent risk factors included age, male, diabetes mellitus, malignancy, low income, baseline pneumonia event, and recent use of oral corticosteroids and aminophylline. In the ICS cohort, while AE rate gradually decreased, the incidence rate of pneumonia significantly increased after ICS use (from 0.10 to 0.21 event/person-year, P  = 0.001). This study demonstrates the association between ICS use and pneumonia in patients with COPD and history of AE. ICS should be judiciously used in indicated COPD patients.